Extraction Of Acetaminophen From Aqueous Solution By Emulsion Liquid Membrane - Zaulkiflee, Nur Dina (2019)
In recent years there is an increasing awareness of pharmaceutical contaminants in the environment. Pharmaceutical contamination in rivers is widespread with hundreds of drugs found at low concentrations. One of the main abundantly used pharmaceuticals are acetaminophen (ACTP). The application of conventional treatment process in wastewater treatment plants is unable to completely remove the residues. Thus, among the existing methods, one of the promising methods for ACTP removal is by emulsion liquid membrane (ELM). ELM comprises internal and membrane phase which form primary W/O (water-in-oil) emulsion. The formulation of ELM was investigated to find suitable carrier, diluent and stripping agent. The effect of emulsion formulation parameters of ELM was investigated in order to obtain its best formulation for removal of ACTP. Selection of suitable ELM components, use of ultrasound emulsification and Taylor-Couette Column (TCC) are expected to increase the extraction efficiency. The influence of several parameters such as carrier, surfactant and stripping agent concentration, ultrasonic power, volume ratio, emulsification time, treat ratio, initial and acid concentration, stirring time and stirring speed were investigated. The results show that kerosene as a diluent, Trioctylamine (TOA) as carrier or extractant and ammonia (NH3) as stripping agent were the most suitable for the liquid membrane formulation of ACTP removal. The optimum condition for the emulsification study was found at 6 wt.% of TOA and Span 80, 0.1 M concentration of stripping agent, 15 minutes of emulsification time, volume ratio of 3:1, 20 W power of ultrasonic probe, 10 ppm of initial concentration, 0.1M of HCl concentration, 5 minutes of extraction time using TCC with a frequency angular ratio of 1.0 and treat ratio of 3:1. The prepared ELM was found to effectively remove 85% of ACTP ions from aqueous solution. Thus, ELM process is a promising technology to extract ACTP from pharmaceutical production wastewater.